Strategi Guru dalam Meningkatkan Nilai Moral pada Anak Usia Dini (5-6) Tahun di RA Arafah Field Kecamatan Medan Area - Suri Rahmadhani, Suri Rahmadhani; Nunzairina, Nunzairina (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Education is a conscious effort or a desire to improve one's own quality from not knowing to knowing. Article one of the National Education System Law (2003) states that education is a conscious and planned effort to create a learning atmosphere and process so that students are active in developing their potential. Therefore, PAUD institutions are very important and valuable investments as well as the foundation for further education. In early childhood education, all children's potential can be optimally developed so that basic behavior and abilities are formed according to their stage of development, so that they are ready to enter further education. In this research at RA Arafah Field, Medan Area sub-district, researchers discovered the phenomenon that the moral values ​​of early childhood at RA Arafah Field were still low. This can be seen from the behavior of children who prefer to play alone regardless of the teacher's instructions in class. In addition, children also prefer to play alone compared to their peers. The type of research used is descriptive qualitative research with a qualitative approach. Data collection techniques through interviews, observation, and documentation through human and non-human data sources. Analysis was carried out during data collection and after all data was collected. Test the validity of the data is done with a standard of credibility. The research results show that in implementing teacher strategies to improve moral values ​​for young children, cooperation or collaboration is needed by teachers, the school and also parents. Because of that the strategy implemented by the teacher has been very effective but has not yet obtained the expected results. There are still many obstacles and several problems in its implementation.